2019
DOI: 10.1002/hep.30208
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin Is Superior to Noradrenaline in the Management of Acute Kidney Injury in Acute on Chronic Liver Failure

Abstract: Acute kidney injury in ACLF carries a high mortality. Infusion of terlipressin gives earlier and higher response than noradrenaline with improved survival in ACLF patients with HRS-AKI. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
179
0
6

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 164 publications
(186 citation statements)
references
References 35 publications
1
179
0
6
Order By: Relevance
“…Terlipressin has been shown to be equally efficacious as norepinephrine in the management of AKI‐HRS, and it is much superior than the midodrine/octreotide combination in improving renal function . However, in the context of ACLF and other organ failures, terlipressin is better than norepinephrine in terms of achieving an earlier and higher response rate in patients with AKI‐HRS …”
Section: Individual Organ Failuresmentioning
confidence: 99%
“…Terlipressin has been shown to be equally efficacious as norepinephrine in the management of AKI‐HRS, and it is much superior than the midodrine/octreotide combination in improving renal function . However, in the context of ACLF and other organ failures, terlipressin is better than norepinephrine in terms of achieving an earlier and higher response rate in patients with AKI‐HRS …”
Section: Individual Organ Failuresmentioning
confidence: 99%
“…In clinical practice, it is quite common for the treating physician to encounter patients who are terlipressin‐intolerant despite using an infusion protocol as suggested by Cavallin et al Profuse diarrhea is one of the most common side effects, leading to stoppage of terlipressin therapy. In the study by Arora et al adverse events requiring discontinuation of the drug were reported in 15% of patients in the terlipressin arm compared to only 8% in the noradrenaline arm. It is this subset of patients which is extremely difficult to manage.…”
mentioning
confidence: 96%
“…I read with great interest the article published recently by Arora et al Hepatorenal syndrome (HRS) is a grave complication occurring in patients with acute on chronic liver failure (ACLF) and is associated with high short‐term mortality. It thus becomes extremely crucial to start appropriate and timely medical therapy in order to reverse this potentially lethal complication.…”
mentioning
confidence: 99%
“…The article by Arora et al compared the use of two vasoconstrictors, terlipressin and noradrenaline, in the management of acute kidney injury in patients with acute on chronic liver failure (ACLF). Numerous other trials have shown no difference between the two when hepatorenal syndrome (HRS) occurred in decompensated cirrhosis .…”
mentioning
confidence: 97%